Perlindungan Hukum terhadap Anak Diluar Perkawinan bagi Tenaga Kerja Wanita di Kabupaten Cianjur - Hazar Kusmayanti; Agus Mulya Karsona (Universitas Serang Raya, 2020)
Protection of female workers in Cianjur District is indeed necessary, especially when working abroad. One of the problems is when there are many migrant workers who give birth to children out of wedlock and return to Indonesia without their husband. The purpose of this study was to determine the legal protection illegitimate child born by Women Workers in Cianjur Regency and to know the role of the government to cope with unmarried children born by Women Workers in Cianjur District. The study was analytical descriptive with the method of this research approach through normative juridical. The results of the study found that legal protection for illegitimate child born by Indonesian Female Workers in Cianjur has a regulation protecting it, namely Article 28 of the 1945 Constitution, Law No. 35 of 2014 concerning Child Protection, Article 43 paragraph (1) of the Marriage Law and Constitutional Court Decision No. 46 / PUU-VIII / 2010. The role of the government in protecting extramarital children born by Indonesian Workers in Cianjur, West Java is not optimal. The role of the village government is very helpful for women migrant workers, namely finding companies that will send their citizens. Whereas illegitimate child born by migrant workers can be protected one of them by smoothing all administrative processes for these children such as issuing a free birth certificate.